2022
DOI: 10.1002/cam4.4662
|View full text |Cite
|
Sign up to set email alerts
|

Changes in parents' psychotropic medication use following child's cancer diagnosis: A fixed‐effects register‐study in Finland

Abstract: Background Symptoms of depression and anxiety are elevated among parents of children with cancer. However, knowledge of parents' psychotropic medication use following child's cancer diagnosis is scarce. Methods We use longitudinal Finnish register data on 3266 mothers and 2687 fathers whose child (aged 0–19) was diagnosed with cancer during 2000–2016. We record mothers' and fathers' psychotropic medication use (at least one annual purchase of anxiolytics, hypnotics, sedatives, or antidepressants) 5 years befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Regarding the status of anxiety and depression among parents of children with cancer, it has been reported that anxiety and depression deteriorate among parents of children with acute lymphoblastic leukemia and central nervous system cancer [ 23 ] ; moreover, it also has been reported that symptoms of anxiety and depression tend to be alleviated over time for parents of child cancer patients from diagnosis to 5 years. [ 17 ] However, the data about the longitudinal change of anxiety and depression among parents of childhood and adolescence patients with osteosarcoma is scarce.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the status of anxiety and depression among parents of children with cancer, it has been reported that anxiety and depression deteriorate among parents of children with acute lymphoblastic leukemia and central nervous system cancer [ 23 ] ; moreover, it also has been reported that symptoms of anxiety and depression tend to be alleviated over time for parents of child cancer patients from diagnosis to 5 years. [ 17 ] However, the data about the longitudinal change of anxiety and depression among parents of childhood and adolescence patients with osteosarcoma is scarce.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature on the impact of child health conditions on parental mental health, effects have been observed when children have life-threatening health conditions like cancer. In such cases, Metsä-Simola et al (2022) found evidence of both an initial shock and persistent strain, particularly among mothers. Increased mental health problems among parents have also been observed when children are diagnosed with less immediately life-threatening but still severe conditions, such as diabetes (Helgeson et al 2012), epilepsy (Carmassi et al 2020;Reilly et al 2018), and inflammatory bowel disease (Baudino et al 2022).…”
Section: Parental Separation Risk Following a Child Health Condition ...mentioning
confidence: 99%
“…Previous research shows that a high proportion of parents of children with cancer report distress, such as anxiety, post‐traumatic stress symptoms, worry, and nervousness 2,3 . The burden of care often places a strain on the well‐being of parents, and, accordingly, an increased risk of psychotropic medication use has been reported, especially among mothers 4,5 . In addition, having a child with cancer may negatively impact levels of income and employment status, which can put further strain on the family 6 .…”
Section: Introductionmentioning
confidence: 99%